Educational tour as awareness strategy for teachers during virtual classes in pandemic - Ugalde Villalobos, María Eugenia (2023)
The Professional Secretarial School (PSS) of the National University of Costa Rica, before the COVID-19 pandemic, as part of an outreach process, conducted two educational tours to the Tele-secondary school of Lanas de Puriscal, San José, Costa Rica. It is located two hours away from the center of this community, with a difficult road to access due to the dirt and mud, where there is hardly any electricity and even less internet in the students' homes. It is worth noting that two of them are now studying at the PSS. PSS professors conducted educational tours to train the students and teachers of that institution in Spanish, English, and Technology topics. However, due to the pandemic, these tours became a sensitization process for some teachers regarding virtual classes, as they were actual witnesses to the situation experienced by these students. Consequently, it is necessary to evaluate the sensitization the teachers underwent and how it modified their behavior with the students from the area during the pandemic. This essay was developed based on the following question: How did the educational tour influence the teachers' treatment of students in virtual classes during the pandemic?